Основы взаимодействия транснациональных корпораций и национальных государств как главных движущих силв современной мировой экономики (Путеводитель предпринимателя)
The article examines the role and importance of transnational corporations in today’s global world economy, as well as their influence on the development of national economies. The authors considered the mechanism of interaction of transnational corporations and nation-states.